Osservazione di uccelli rari in Sardegna - Torre, Antonio (Gallizzi, 1983)
The authors refer to certain sightings of rare birds for Sardinia.The Species observed are: Storm Petrel, Gannet, White Stork, Blak Stork, Great Skua. It was also reported on breeding of Storm Petrel on a small island in the north-west of Sardinia.